2018
DOI: 10.4093/dmj.2017.0102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Socioeconomic Status on Health Behaviors, Metabolic Control, and Chronic Complications in Type 2 Diabetes Mellitus

Abstract: BackgroundThe aim of the study was to assess the impact of socioeconomic status (SES) on health behaviors, metabolic control, and chronic complications in people with type 2 diabetes mellitus (T2DM) from South Korea, a country with universal health insurance coverage and that has experienced rapid economic and social transition.MethodsA total of 3,294 Korean men and women with T2DM aged 30 to 65 years, participating in the Korean National Diabetes Program (KNDP) cohort who reported their SES and had baseline c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…Previous studies have shown that people with low socioeconomic status (SES) were more likely to develop type 2 diabetes with worse glycemic control that can lead to more diabetic complications [1314]. According to the Korean National Diabetes Program (KNDP) cohort study, men with low SES had worse glycemic control and higher risk for retinopathy [15]. In addition, in Korea, low-income people with diabetes had lower medication adherence and lower levels of utilization of fundus examinations and HbA1c tests than high-income people with diabetes [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that people with low socioeconomic status (SES) were more likely to develop type 2 diabetes with worse glycemic control that can lead to more diabetic complications [1314]. According to the Korean National Diabetes Program (KNDP) cohort study, men with low SES had worse glycemic control and higher risk for retinopathy [15]. In addition, in Korea, low-income people with diabetes had lower medication adherence and lower levels of utilization of fundus examinations and HbA1c tests than high-income people with diabetes [16].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the results of other studies. It is well-documented that a low socioeconomic status (education level and income) has a significant impact on the incidence of obesity, diabetes, and cardiovascular disease [27][28][29]. In the cross-sectional EUROASPIRE IV study, which was undertaken in 24 European countries, a higher level of education was found to have a significant impact on the control of risk factors in patients with coronary heart disease, such as currently smoking, being overweight, obesity, a low level of physical activity, low HDL-C, hypertension, and diabetes [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, T2DM women and men with lower income and education level show poor food choice revealing higher carbohydrate and lower fat intake. Considering the sex-related difference in insulin sensitivity, it is clear how sociodemographic aspects may interact with biology [ 61 ]. This association has been observed also in pregnant woman [ 62 ].…”
Section: Sex Hormones In Endocrine Gender-related Differencesmentioning
confidence: 99%